Professionalization of the Foreign Service of the Argentine Nation: Peronism and the first comprehensive regulation of the diplomatic career (Res Gesta, 2021)
This paper will address how the professionalization and organization of the Argentine Foreign Service were developed from the study of the legislation that ruled the diplomatic personnel. It will emphasise fundamentally on the reforms introduced by Juan Domingo Peron’s government, which are the first integral regulation of the organism, and their development until the modifications introduced by the Liberator Revolution. Based on these normative changes, we look at connexion points between them and the emergence of new diplomatic profiles.
Keywords: Foreign Service; Peronism; Legislation; Professionalization